Liquid-Liquid Successive Fractionation of Stem Bark Alcoholic Extract from Acacia polyacantha: GC-MS Analysis and Antibacterial Activities. - Hammad, Abubakr Alsiddeg; Abdelgadir, Abdelgadir A.; Yassin, Sitelbanat; Ahmed, Elhadi M. (African Pharmaceutical Journal, 2022)
Antimicrobial resistance is considered as one of the top problematic issues facing world health system. Fortunately, medicinal plants, considered as ongoing source of antimicrobial agents can resolve this health problem Acacia polyacantha tree (AL-Kakamout) is widely available in Sudan. It is one of the main sources of Gum Arabic and used traditionally for treating many bacterial diseases. This study aimed to analyze the fractions of hydro-ethanol extract of A. polyacantha stem bark obtained by liquid-liquid successive fractionation by GC-MS method and to determine the antibacterial activity of these fractions against two standard bacterial strains of Gram-positive bacteria Staphylococcus aureus (ATCC 25923) and Gram-negative bacteria Pseudomonas aeroginosa (ATCC 27853) by well diffusion technique. The powdered A. polyacantha stem bark was extracted by cold maceration using 70% Ethanol and successively fractionated to produce petroleum ether, butanol and aqueous fraction. The butanol fraction in which Cyclolanostanol acetate (28.29%), Dopamine, N,N-dimethyl-, dimethyl ether (21.94%), were dominating, was the most active against both bacterial strains. Petroleum ether fraction which is rich in Lupeol, trifluoroacetate (37.64%) and stigmasterol (13.05%) triterpenoids was found to be more active against P. aeroginosa and with less activity against S.aureus. While the remaining aqueous fraction where hordenine alkaloid (47.21%) and 3-O-Methyl-d-glucose (%30.46) were dominant components showed no activity against S.aureus and with low activity against P. aeroginosa . In conclusion, A.polyacantha bark extract fractions are rich in phytochemical compounds having antibacterial activity and highly recommended to be further investigated as potential antibacterial agents.